The Smad3-dependent microRNA let-7i-5p promoted renal fibrosis in mice with unilateral ureteral obstruction - Peng, Ze; Guo, Huai-Ying; Li, Yu-Qing; Li, Jian-Chun; Yang, Xiao-Hong; Liu, Jian; Hu, Qiong-Dan; Wang, Hong-Lian; Wang, Li (Frontiers in Physiology, 2022)
Renal fibrosis is a common feature of all types of chronic kidney disease (CKD) and is tightly regulated by the TGF-β/Smad3 pathway. Let-7i-5p belongs to the let-7 microRNA family with diverse biological functions. It has been reported that let-7i-5p suppresses fibrotic disease in the heart, lungs, and blood vessels, while the role of let-7i-5p in renal fibrosis remains limited. In this study, we aimed to investigate the role of let-7i-5p in renal fibrosis in a mouse model of unilateral ureteral obstruction (UUO) and TGF-β1–stimulated renal tubular cell line TCMK1. The RNA-targeting CRISPR/Cas13d system was used to knock down let-7i-5p. Renal injury and fibrosis were determined by histological analysis, RT-PCR, Western blot, and immunostaining. Our results have shown that in the kidneys after UUO, the expression of let-7i-5p was significantly increased along with notable tubular injury and interstitial fibrosis. Electroporation of let-7i–targeting Cas13d plasmid efficiently knocked down let-7i-5p in kidneys after UUO with reduced tubular injury, fibrotic area, and expression of fibrotic marker genes α-SMA, fibronectin, and Col1a1. In TGF-β1–stimulated TCMK1 cells, knockdown of let-7i-5p by Cas13d plasmid transfection also blunted the expression of fibrotic marker genes. Most importantly, the genomic locus of let-7i showed enriched binding of Smad3 as revealed by chromatin immunoprecipitation. In TCMK1 cells, the overexpression of Smad3 can directly induce the expression of let-7i-5p. However, the deletion of Smad3 abolished TGF-β1–stimulated let-7i-5p expression. Collectively, these findings suggest that let-7i-5p is a Smad3-dependent microRNA that plays a pathogenic role in renal fibrosis. Let-7i-5p could be a promising target for the treatment of CKD-associated renal fibrosis.